Plasma soluble α-klotho protein levels in premature and term neonates: correlations with growth and metabolic parameters. - Tania Siahanidou; Garatzioti, Maria; Lazaropoulou, Christina; Kourlaba, Georgia; Papassotiriou, Ioannis; Kino, Tomoshige; Imura, Akihiro; Nabeshima, Yo-ichi; Chrousos, George (Eur J Endocrinol, 2012)
{OBJECTIVE: α-Klotho (α-KL), a protein with antiaging properties, regulates phosphate, calcium, and bone metabolism, induces resistance to oxidative stress, and may participate in insulin signaling. The role of α-KL in neonates, known to be prone to metabolic disturbances and oxidative stress, is not known. The aim of this study was to evaluate circulating soluble α-KL concentrations in preterm and full-term neonates and unravel possible correlations with growth, metabolism, and indices of oxidative stress. DESIGN: Prospective study. METHODS: Plasma-soluble α-KL levels were determined by specific ELISA in 50 healthy neonates (25 preterm, mean (s.d.) gestational age (GA) 33.7 (1.1) weeks, and 25 full-term infants) at days 14 and 28 of life. Associations of α-KL with anthropometric, metabolic parameters, and indices of oxidative stress were examined. RESULTS: α-KL levels were significantly higher in full-term than in preterm infants at both days 14 (1099 (480) pg/ml vs 884 (239) pg/ml respectively; P<0.05) and 28 (1277 (444) pg/ml vs 983 (264) pg/ml respectively; P<0.01). In both preterm and full-term infants, α-KL levels increased significantly from day 14 to 28 of life (P<0.001). Circulating α-KL concentrations correlated with GA (β=0.32
Keywords: Age Factors; Biological Markers; Child Development; Energy Metabolism; Female; Glucuronidase; Humans; Infant; Male; Newborn; Oxidative Stress; Premature